Homophily and its effects on collaborations and repeated collaborations: A study across scientific fields - Santos, J. M. (2024)
This study examines the influence of homophily on research collaborations across all scientific fields, noting the role of ascribed, acquired, geographical, current career, and educational and career history attributes. Our analysis builds on previous studies by adopting a comparative approach across scientific fields and examining the effect of homophily on repeated collaborations. Our findings reveal physical proximity as a universal driver of collaboration across all scientific fields, both for overall collaborations and as a maintainer of collaborative endeavors. We also note that most attributes that are responsible for overall collaborations are similar to the attributes that play a role in maintaining them, with a few exceptions, notably when it comes to institutional characteristics. Our results also show the complex role of career history attributes, such as job variety and international mobility, in influencing the likelihood of collaboration. This study sheds light on the intricate interplay of different attributes in shaping scientific collaborations, underscoring the need for a multidisciplinary approach in future homophily studies and nuanced strategies for fostering collaborations across different scientific fields.